2016
DOI: 10.1016/j.rbre.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

IL33 in rheumatoid arthritis: potential contribution to pathogenesis

Abstract: A better understanding of the inflammatory mechanisms of rheumatoid arthritis and the development of biological therapy revolutionized its treatment, enabling an interference in the synovitis - structural damage - functional disability cycle. Interleukin 33 was recently described as a new member of the interleukin-1 family, whose common feature is its pro-inflammatory activity. Its involvement in the pathogenesis of a variety of diseases, including autoimmune diseases, raises the interest in the possible relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…115 In addition to a role for IL-33 in the Th2 paradigm, there are also studies revealing a role for IL-33 in classic Th1 diseases such as inflammatory bowel disease 116 and rheumatoid arthritis. 117,118 IL-33 also increases the production of IFNγ. 119…”
Section: Nuclear Function Of Il-33mentioning
confidence: 95%
See 1 more Smart Citation
“…115 In addition to a role for IL-33 in the Th2 paradigm, there are also studies revealing a role for IL-33 in classic Th1 diseases such as inflammatory bowel disease 116 and rheumatoid arthritis. 117,118 IL-33 also increases the production of IFNγ. 119…”
Section: Nuclear Function Of Il-33mentioning
confidence: 95%
“…Another mechanism for the anti‐inflammatory properties of IL‐33 appears to be due to the requirement for IL‐1R8 . In addition to a role for IL‐33 in the Th2 paradigm, there are also studies revealing a role for IL‐33 in classic Th1 diseases such as inflammatory bowel disease and rheumatoid arthritis . IL‐33 also increases the production of IFN‐γ …”
Section: Il‐33mentioning
confidence: 99%
“…5,23 IL-33, mainly produced by airways epithelial cells, fibroblasts and endothelial cells as well as activated immune cells, 24 plays important roles in a range of autoimmune diseases. [25][26][27][28] In an attempt to link these findings, and in particular to provide a possible explanation for why lung function impairment and particularly alveolar damage may persist and progress despite apparent removal of the provoking stimulus, we hypothesized that the respiratory epithelial alarmin IL-33, known to be produced in response to inhaled environmental insults such as cigarette smoke, triggers a humoral autoimmune response directed against alveolar epithelial cells. Our aim was to explore whether antibodies can be induced in mice immunized with autologous (syngeneic) normal lung tissue while exposed to exogenous IL-33 delivered topically to the airways or systemically, and to examine their specificity in mice as well as their cross-specificity for human alveolar epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that COPD is characterized by elevated production of the alarmin cytokine IL‐33, particularly with continued cigarette smoke exposure, to a degree that correlates with the rate of progression of the disease . IL‐33, mainly produced by airways epithelial cells, fibroblasts and endothelial cells as well as activated immune cells, plays important roles in a range of autoimmune diseases …”
Section: Introductionmentioning
confidence: 99%
“…Symmetry is a fundamental feature DOI 10.5935/2595-0118.20200003 ORIGINAL ARTICLE of the disease that evolves from asymmetric to symmetrical, with the progression of pathological manifestations. Initial inflammatory events affect the synovial membrane, presenting cellular hyperplasia and intense inflammatory process, denoting synovitis 2 . The synovial membrane has innervation marked by the presence of positive nerve fibers for proinflammatory neuropeptides, such as substance P (sP) and calcitonin gene-related peptide (CGRP), both in the intimal and subintimal layers and around the blood vessels 3 .…”
Section: Introductionmentioning
confidence: 99%